Catalisadores Ni/BaO-Al2O3 e Ni/BaO-SiO2 para reforma do metano com CO2 - Almeida, Janete Cavalcante (2012)
In this work the activity of nickel catalysts were appraised regarding the dry reforming of methane. Due to the low surface area, the catalysts were supported on SiO2 and Al2O3, in order to verify the effect of the support on the catalytic activity. For that, catalysts 12%Ni/xOBa/SiO2 and 12%Ni/xOBa/Al2O3 (x=6, 8 and 12%) were prepared, characterized and submitted to catalytic assays in the methane reforming reaction with carbon dioxide, with the objective of evaluating the effect of the addition of barium to the support. The catalysts were prepared by the wet impregnation method and characterized by powder x-ray diffraction, nitrogen physisorption by the B.E.T.method, area, volume and pore radius, temperature programmed reduction with H2 and X-ray fluorescence. The catalytic assays showed that all the catalysts were shown active in the dry reforming of methane and the conversion of the products was dependent on the type of catalyst appraised. According to the obtained results, they stand out the catalysts with 12% barium in mass addition supported on SiO2 as well as Al2O3.